"Megalosaurus cf. superbus" from southeastern Romania: The oldest known Cretaceous carcharodontosaurid (Dinosauria: Theropoda) and its implications for earliest Cretaceous Europe-Gondwana connections. (May 2016) - Csiki-Sava, Zoltán; Brusatte, Stephen L.; Vasile, Ştefan
Abstract: Some of the best records of continental vertebrates from the Cretaceous of Europe come from Romania, particularly two well-known occurrences of dwarfed and morphologically aberrant dinosaurs and other taxa that lived on islands (the Cornet and Haţeg Island faunas). Substantially less is known about those vertebrates living in the more stable, cratonic regions of Romania (and Eastern Europe as a whole), particularly during the earliest Cretaceous. We describe one of the few early Early Cretaceous fossils that have ever been found from these regions, the tooth of a large theropod dinosaur from Southern Dobrogea, which was discovered over a century ago but whose age and identification have been controversial. We identify the specimen as coming from the Valanginian stage of the Early Cretaceous, an incredibly poorly sampled interval in global dinosaur evolution, and as belonging to Carcharodontosauridae, a clade of derived, large-bodied apex predators whose earliest Cretaceous history is poorly known. Quantitative analyses demonstrate that the Romanian tooth shows affinities with a derived carcharodontosaurid subgroup, the Carcharodontosaurinae, which until now has been known solely from Gondwana. Our results suggest that this subgroup of colossal predators did not evolve vicariantly as Laurasia split from Gondwana, but originated earlier, perhaps in Europe. The carcharodontosaurine diversification may have been tied to a north-to-south trans-Tethyan dispersal that took place sometime between the Valanginian and the Aptian, illustrating the importance of palaeogeographic ties between these two realms during the largely mysterious early–mid Early Cretaceous. Graphical abstract: Highlights: An isolated, large theropod dinosaur tooth from Romania is referred to Carcharodontosauridae. The Romanian carcharodontosaurid is Valanginian in age, the oldest Cretaceous record of the clade. This occurrence supports dispersal from Europe to west-Gondwana during the mid-Early Cretaceous.